Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Connect with professionals on our platform to receive accurate answers to your questions quickly and efficiently. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

a) Simplify the expression:
[tex]\[ 4a + 7b + 5a - b \][/tex]

b) Simplify the expression:
[tex]\[ 6c + 4d - c - 7d \][/tex]


Sagot :

Sure, let's work through the problem step by step for both parts:

### Part a: [tex]\(4a + 7b + 5a - b\)[/tex]

1. Combine like terms (terms involving [tex]\(a\)[/tex] and terms involving [tex]\(b\)[/tex]):
- Look at the terms involving [tex]\(a\)[/tex]: [tex]\(4a\)[/tex] and [tex]\(5a\)[/tex].
- Combine them: [tex]\(4a + 5a = 9a\)[/tex].

2. Next, look at the terms involving [tex]\(b\)[/tex]:
- The terms involving [tex]\(b\)[/tex] are [tex]\(7b\)[/tex] and [tex]\(-b\)[/tex].
- Combine them: [tex]\(7b - b = 6b\)[/tex].

3. Combine the results:
- Put together the combined terms involving [tex]\(a\)[/tex] and [tex]\(b\)[/tex]: [tex]\(9a + 6b\)[/tex].

So, [tex]\(4a + 7b + 5a - b = 9a + 6b\)[/tex].

To further simplify using specific values for [tex]\(a\)[/tex] and [tex]\(b\)[/tex], let's assume [tex]\(a = 1\)[/tex] and [tex]\(b = 1\)[/tex]:
[tex]\[ 9a + 6b = 9(1) + 6(1) = 9 + 6 = 15 \][/tex]

### Part b: [tex]\(6c + 4d - c - 7d\)[/tex]

1. Combine like terms (terms involving [tex]\(c\)[/tex] and terms involving [tex]\(d\)[/tex]):
- Look at the terms involving [tex]\(c\)[/tex]: [tex]\(6c\)[/tex] and [tex]\(-c\)[/tex].
- Combine them: [tex]\(6c - c = 5c\)[/tex].

2. Next, look at the terms involving [tex]\(d\)[/tex]:
- The terms involving [tex]\(d\)[/tex] are [tex]\(4d\)[/tex] and [tex]\(-7d\)[/tex].
- Combine them: [tex]\(4d - 7d = -3d\)[/tex].

3. Combine the results:
- Put together the combined terms involving [tex]\(c\)[/tex] and [tex]\(d\)[/tex]: [tex]\(5c - 3d\)[/tex].

So, [tex]\(6c + 4d - c - 7d = 5c - 3d\)[/tex].

To further simplify using specific values for [tex]\(c\)[/tex] and [tex]\(d\)[/tex], let's assume [tex]\(c = 1\)[/tex] and [tex]\(d = 1\)[/tex]:
[tex]\[ 5c - 3d = 5(1) - 3(1) = 5 - 3 = 2 \][/tex]

### Summary
- For part a, [tex]\(4a + 7b + 5a - b = 15\)[/tex] when [tex]\(a = 1\)[/tex] and [tex]\(b = 1\)[/tex].
- For part b, [tex]\(6c + 4d - c - 7d = 2\)[/tex] when [tex]\(c = 1\)[/tex] and [tex]\(d = 1\)[/tex].

So, the final results are:
[tex]\[ \text{Part a: } 15 \][/tex]
[tex]\[ \text{Part b: } 2 \][/tex]